Cochlear Implantation in Adults With Single‐Sided Deafness: A Systematic Review and Meta‐analysis. (26th January 2023) - Oh, Samuel J.; Mavrommatis, Maria A.; Fan, Caleb J.; DiRisio, Aislyn C.; Villavisanis, Dillan F.; Berson, Elisa R.; Schwam, Zachary G.; Wanna, George B.; Cosetti, Maura K.
Abstract: Objective: To determine the clinical outcomes of adult patients with single‐sided deafness (SSD) undergoing ipsilateral cochlear implantation. Data Source: An electronic search of Medline and Embase articles. Review Methods: A systematic review was performed with a search strategy developed by a licensed librarian to identify studies of adult patients with SSD who underwent ipsilateral cochlear implantation. Articles were managed in Covidence and evaluated by 2 independent reviewers. Risk of bias was assessed and data were extracted, including patient demographics, etiology of deafness, duration of deafness, and postoperative change in speech recognition, tinnitus, sound localization, and quality of life (QoL). A meta‐analysis was performed, and pooled mean differences were calculated for each outcome of interest via random effects models by each outcome, as well as subgroup analyses by the individual clinical score used. Results: Of 2309 studies identified, 185 full texts were evaluated, and 50 were ultimately included involving 674 patients. Speech perception scores in quiet and noise, tinnitus control, sound localization, and QoL all significantly improved after implantation. Pooled outcomes demonstrated score improvements in speech perception (standardized mean difference [SMD], 2.8 [95% CI, 2.16‐3.43]), QoL (SMD, 0.68 [95% CI, 0.45‐0.91]), sound localization (SMD, −1.13 [95% CI, −1.68 to −0.57]), and tinnitus score reduction (SMD, −1.32 [95% CI, −1.85 to −0.80]). Conclusions: Cochlear implantation in adults with SSD results in significant improvements in speech perception, tinnitus control, sound localization, and QoL. Level of evidence: 2.